A subnational assessment of hotel social media metrics - the case of Serbia - Kalinić, Časlav; Vujičić, Miroslav (Geographica Pannonica, 2019)
Facebook is the most widely used SNS (Social Networking Sites) platform globally, and it represents an important marketing and communication channel for hotels. The dynamic and constantly changing nature requires continuous adaptation to changes and benchmarking in order to identify best practices. This paper investigates selected characteristics of Facebook pages (social media metrics) of all hotels in Serbia in national regional context. In the case of four explored regions of Serbia, the results indicate regional inconsistencies, with most notable differences within the number of page fans, temporal aspects of posts as well as user engagement. On the other hand, similarities are evident in some post characteristics such as type of post and post length, while a specific pattern can be observed concerning page fans country of origin. This paper contributes to the regional understanding of social media metrics that can help hotels when assessing their promotional activities.